2012
DOI: 10.1093/cid/cir996
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster of Pneumocystis Infections Among Renal Transplant Recipients: Molecular Evidence of Colonized Patients as Potential Infectious Sources of Pneumocystis jirovecii

Abstract: The results provide to our knowledge the first data on the role of colonized patients as potential sources of P. jirovecii in a context of nosocomial acquisition of the fungus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 38 publications
4
60
1
Order By: Relevance
“…In addition, our findings clearly support the conclusion that liver transplant patients P1 to P4 were all infected by a single genotype of P. jirovecii. This conclusion seems robust because, as shown by the phylogenetic tree, data for the three loci combined were sufficient to discriminate between 24 unrelated P. jirovecii isolates (10). To our knowledge, this is the first genotypic demonstration of clustered PCP limited only to liver transplant patients (24), whereas numerous studies have reported similar findings for kidney recipients (6,10,18), especially in France (10).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In addition, our findings clearly support the conclusion that liver transplant patients P1 to P4 were all infected by a single genotype of P. jirovecii. This conclusion seems robust because, as shown by the phylogenetic tree, data for the three loci combined were sufficient to discriminate between 24 unrelated P. jirovecii isolates (10). To our knowledge, this is the first genotypic demonstration of clustered PCP limited only to liver transplant patients (24), whereas numerous studies have reported similar findings for kidney recipients (6,10,18), especially in France (10).…”
Section: Discussionsupporting
confidence: 62%
“…It is responsible for a severe respiratory disease, Pneumocystis jirovecii pneumonia (PCP) (1,20). One potential route of infection is currently believed to be patient-to-patient transmission mediated by airborne droplets (1), and the hypothesis related to contamination from an environmental source has largely been rejected (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the fungus may play a role in the progression of underlying lung diseases or in the development of PCP in colonized patients (4). It also has been recently shown that colonized patients may act as potential infectious sources (37).…”
Section: Discussionmentioning
confidence: 99%